Médias, ethnomarketing et segmentation de l’espace public - Isabelle Rigoni (Tic & Société)
The democratisation of access to new ICTs has helped diversify the expressions and use of the ethnic media. The diversification of the ethnic media encouraged identity entrepreneurs to use the specialised media to serve ads and information about their products and goods. This paper outlines the implications of the commodification of identity and ethnic marketing in the media, particularly in terms of segmentation of productions and audiences. The increasing specialisation of ethnic media, as part of a general trend, helps to fuel a new public communicative space. In this context, the challenge for the CIS is to conceptualize contemporary transformations of public space by trying to overcome the utopic idea of universal accessibility to ICTs, as well as more pessimistic visions of the communautarisation of public space.